2022
DOI: 10.1002/cbin.11767
|View full text |Cite
|
Sign up to set email alerts
|

IL‐17 in intervertebral disc degeneration: Mechanistic insights and therapeutic implications

Abstract: Intervertebral disc degeneration (IDD) serves as an independent risk factor for lower back pain and is closely associated with spinal musculoskeletal disorders, including lumbar disc herniation, radiculopathy, and myelopathy. , also named IL-17A, is a critical signature cytokine of T-helper 17 cells. Upon binding to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 150 publications
0
16
0
Order By: Relevance
“…Using the Venn diagram, there were 42 co-DEGs in annulus cells induced by TNF-α and IL-1β, which were mainly enriched in the response to LPS and molecules of bacterial origin and the regulation of receptor ligand activity and signaling receptor activator activity according to GO analysis. In addition, the following signaling pathways enriched through KEGG analysis, mainly including TNF signaling pathway [33], IL-17 signaling pathway [34], NF-κB signaling pathway [35], and NOD-like receptor signaling pathway [36], play crucial roles in the activity of catabolic genes and inflammatory mediators during the pathological process of IVDD as demonstrated by previous researche. Furthermore, a PPI network based on co-DEGs was constructed to obtain the hub genes (CXCL1, CXCL2, CXCL8, IL1β, and PTGS2).…”
Section: Discussionmentioning
confidence: 99%
“…Using the Venn diagram, there were 42 co-DEGs in annulus cells induced by TNF-α and IL-1β, which were mainly enriched in the response to LPS and molecules of bacterial origin and the regulation of receptor ligand activity and signaling receptor activator activity according to GO analysis. In addition, the following signaling pathways enriched through KEGG analysis, mainly including TNF signaling pathway [33], IL-17 signaling pathway [34], NF-κB signaling pathway [35], and NOD-like receptor signaling pathway [36], play crucial roles in the activity of catabolic genes and inflammatory mediators during the pathological process of IVDD as demonstrated by previous researche. Furthermore, a PPI network based on co-DEGs was constructed to obtain the hub genes (CXCL1, CXCL2, CXCL8, IL1β, and PTGS2).…”
Section: Discussionmentioning
confidence: 99%
“…The most enriched biological process was Response to oxidative stress, cellular component was Cytoplasm, and molecular function was Identical protein binding. More importantly, we also investigated the potential signaling pathways involved in the repair process of NPCs cocultured with MSCs, and some of these signaling pathways have been proved to play important roles in the pathophysiology of IDD [38][39][40][41][42]. TNF signaling pathway and IL-17 signaling pathway both were inflammation-related pathways, which indicated that MSCs might reduce the oxidative stress, and then improve the inflammatory status of degenerative NPCs [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, we also investigated the potential signaling pathways involved in the repair process of NPCs cocultured with MSCs, and some of these signaling pathways have been proved to play important roles in the pathophysiology of IDD [38][39][40][41][42]. TNF signaling pathway and IL-17 signaling pathway both were inflammation-related pathways, which indicated that MSCs might reduce the oxidative stress, and then improve the inflammatory status of degenerative NPCs [38,39]. MAPK signaling pathway was another vital biolog-ical pathway in the development of IDD [40][41][42] 7 Stem Cells International degenerative NPCs cocultured with MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ was reported to affect tissue-specific macrophages in NP. Furthermore, several angiogenic and neurogenic factors have also been linked to the degeneration of IVDs, conducting to blood vessels and nerve in-growth [ 12 , 20 , 25 , 26 , 27 , 28 ].…”
Section: Pathogenesis and Etiology Of Intervertebral Disc Degenerationmentioning
confidence: 99%